Analisis Faktor yang Mempengaruhi Produktivitas Tenaga Kerja dengan Fuzzy AHP pada Proyek Bantalan Beton Divre IV Tanjungkarang - Putri, Wanda Noor Amalia; Usman, Kristianto; Siregar, Amril Ma’ruf (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
Economic growth in a country can be reflected by the number of construction projects. To achieve robust economic growth, effective human resource management is required to enhance productivity. One aspect that affects work productivity is the labor force. This research aims to analyze the factors and tasks that influence labor productivity in Concrete Bearing Replacement Projects. Given the many factors or criteria to consider, the Fuzzy Analytical Hierarchy Process (Fuzzy AHP) method is used for identification. The Fuzzy AHP method assists in evaluating various criteria and determining the relative weights of each factor to make informed decisions. To simplify the analysis, 4 criteria and 12 sub-criteria are used. Based on the analysis, the factor with the greatest impact on labor productivity is the work area (K2-1) with a weight of 0.1327, while the factor with the lowest weight is the accuracy of material delivery to the location (A2) with a weight of 0.0442. The tasks that relatively impact labor productivity include loading and unloading concrete bearings (A3) with a weight of 0.0029, replacing concrete bearings with a weight value of 0.0026, and the lowest impact tasks are dismantling gongsol and revising curves, with a weight value of 0.0022.